2009
DOI: 10.1592/phco.29.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban: A Novel, Oral, Direct Factor Xa Inhibitor

Abstract: Thromboembolic disorders such as deep vein thrombosis, pulmonary embolism, myocardial infarction, and stroke often result in long-term disability and/or mortality. The anticoagulants currently available have been effective in the treatment and prevention of these disorders; however, parenteral administration, variable pharmacokinetics and pharmacodynamics, drug and dietary interactions, and a requirement for frequent monitoring of efficacy and safety limit use of these drugs. Rivaroxaban is a novel, oral facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…The half-life is 5 hours to 9 hours in healthy adults aged 20 years to 45 years and 11 hours to 19 hours in the elderly. 3 There is no widely supported antidote, although Rivaroxaban was approved by the FDA in 2011 for the prevention of blood clots after hip and knee replacement and for the prevention of stroke in patients with nonvalvular atrial fibrillation. In clinical trials, Wasserlauf et al 5 reported major bleeding as the most common side effect, occurring in up to 5.6% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The half-life is 5 hours to 9 hours in healthy adults aged 20 years to 45 years and 11 hours to 19 hours in the elderly. 3 There is no widely supported antidote, although Rivaroxaban was approved by the FDA in 2011 for the prevention of blood clots after hip and knee replacement and for the prevention of stroke in patients with nonvalvular atrial fibrillation. In clinical trials, Wasserlauf et al 5 reported major bleeding as the most common side effect, occurring in up to 5.6% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In prevention, they have been shown to produce overall benefit by reducing the incidence of AIS in high-risk patient populations. However, despite relentless efforts and numerous clinical trials with antithrombotic agents and protocols to treat AIS, many approaches have failed primarily due to serious bleeding side effects, including hemorrhagic transformation and intracerebral hemorrhage, that outweigh the antithrombotic benefit [18-21, 25]. The most recent rational strategy to inhibit thrombogenesis in stroke involves identifying and targeting those prothrombotic functions of platelets and coagulation factors that are not essential for hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…38 In healthy individuals, rivaroxaban has an average half-life of 10 hours and is eliminated through both hepatic metabolism and renal excretion (33% and 66%, respectively). 38 As with other direct FXa inhibitors, rivaroxaban has been demonstrated to block both free and clot-bound FXa. 39, 40 Rivaroxaban may interact with both CYP3A4/5 and P-gp activators as well as inhibitors.…”
Section: Mechanism Of Action and Pharmacology (Table 1)mentioning
confidence: 99%
“…It was first approved for VTE prophylaxis in patients undergoing THR or TKR. 38,42,44,45,46,47 Based on results from the ROCKET AF trial, rivaroxaban was then approved for prevention of ischemic stroke and SE in patients with NVAF. 42,43 Finally, rivaroxaban received approval for treatment and then secondary prevention of acute DVT and PE.…”
Section: Clinical Indications and Contraindicationsmentioning
confidence: 99%